The role of nitric oxide in an experimental necrotising enterocolitis model - Muazez Cevik; Cetin Ali Karadag; Damlanur Ertem Sakiz; Burak Tander; Didem Daskin Embleton (African Journal of Paediatric Surgery, 2013)
Background: Necrotising enterocolitis (NEC) causes a significant life-threatening gastrointestinal system (GIS) disease with severe mortality and morbidity, particularly in premature infants. Nitric oxide (NO) has many functions in the GIS. Therefore, in the present study, we evaluated the effects of NO in experimentally induced NEC of newborn 1-day-old rats following hypoxia/reoxygenation (HR). Materials and Methods: Thirty Wistar albino rats (weight, 5-8 g) were randomly divided into three groups: group 1 (HR), group 2 (HR + nitroglycerine), and group 3 (control). HR was achieved by placing the rat in carbon dioxide (CO2) for five minutes at 22°C, which was followed by five minutes of 100% oxygen. After HR, nitroglycerine was administered for three days at 50 μg/Kg/day. On day 4, the rats were decapitated and the intestines between the duodenum and sigmoid colon were resected and histopathologically examined. Results: The histopathological findings of groups 1 and 2 were characteristic of NEC. Intestinal injury in group 1 was significantly more prevalent than that in group 2 (χ2 = 21.55, P = 0.000). The intestinal injury score in group 3 was significantly lower than that in the other groups (P < 0.05). Conclusions: NO treatment was effective for treating experimentally induced NEC.